The effectiveness of sports and health tourism in organising student recreation in the subtropical climate zone - Grigorev, V.I.; Kiprushina, I.I.; Bulavchenko, K.V.; Rozanova, L.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to optimise students' summer holidays in the subtropical climate zone through the targeted use of sports and health tourism. Methods and structure of the study. The research was conducted between 24 June and 14 July 2025 at Adlerkurort in Sochi on the platform of the Centre for Innovative Tourism Development of St. Petersburg State Economic University. A total of 135 students, 52 males and 83 females, aged 18-19, were examined. Functional status was assessed using the Ruffier test, the Stange test, PWC170, HR, and BP. Results and conclusions. The authors developed a multi-purpose programme lasting 21 days, including 12 training sessions conducted on mountain routes of 3, 5 and 7 km in subtropical climatic conditions. The data obtained in the course of the study prove that in subtropical conditions, tourism accelerates the processes of restoring activity, working capacity and adaptive reserves.